2019
DOI: 10.1002/dmrr.3141
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis on the association between the frequency of tooth brushing and diabetes mellitus risk

Abstract: Background and Objective: Epidemiological studies suggested that the frequency of tooth brushing might be associated with the risk of diabetes mellitus (DM), but the results were inconsistent, and no systematic review was conducted to focus on this topic. In this meta-analysis, we synthesized available observational epidemiological evidences to identify the association between tooth brushing and DM risk and investigate the potential dose-response relationship of them. Methods: We searched PubMed and Embase fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
5
11
1
Order By: Relevance
“…Our overall findings are in line with other systematic reviews and meta-analyses that demonstrated an association between oral health or hygiene and metabolic conditions [9,37]. Poor oral hygiene not only leads to dental infections, such as periodontitis, but it may also affect systemic health [55].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our overall findings are in line with other systematic reviews and meta-analyses that demonstrated an association between oral health or hygiene and metabolic conditions [9,37]. Poor oral hygiene not only leads to dental infections, such as periodontitis, but it may also affect systemic health [55].…”
Section: Discussionsupporting
confidence: 91%
“…The OR was used as the common measure for the association between oral hygiene and MetS. The reported RR was considered approximately as OR [37]. The data utilized in the meta-analysis were the estimates and the corresponding 95% CI from the most adjusted model in the studies.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of observational studies published in 2019 examined the relationship between frequency of tooth brushing and diabetes mellitus and concluded that people who brush their teeth more frequently are less likely to develop diabetes mellitus (Fu et al 2019). In a cohort study conducted in Japan, less frequency of tooth brushing was significantly associated with diabetes mellitus in men and dyslipidemia in women, while there was no significant association between frequency of tooth brushing and hypertension (Kuwabara et al 2017).…”
Section: Brushing Teeth After Mealsmentioning
confidence: 99%
“…Past studies have shown that increasing the frequency of toothbrushing lowers the risk of cardiovascular events [22] and T2DM [23] and may improve the condition of rheumatoid arthritis [24]. The anti-inflammatory effect of the removal of bacterial plaque is assumed to be the reason for these systemic positive effects.…”
Section: Introductionmentioning
confidence: 99%